Analisis Kualitas Manajemen Bandwitdh Layanan Jaringan Internet di Institut Shanti Bhuana - Maya Sari; Carolus Ningki; Fenni Rosa; Kristian Novando; Yohanes Duhin Mukin (Institut Shanti Bhuana, 2023)
To test the quality of internet network services at the Shanti Bhuana Institute and the addition of two study programs, namely Information Technology S1 and PGSD S1 in August 2020. During this pandemic, advances in information technology, especially in the internet sector, network service quality, and system services are very important, especially when it comes to accessing online applications like Zoom or Google Meet. The internet network of the Shanti Bhuana Institute was initially only 10 Mbps, but was later increased to 130 Mbps. The author will analyze the quality of bandwidth management of internet network services at the Shanti Bhuana Institute. Based on these problems, the authors will use the FDMI (Fixed Daily Measurement Interval) and Qos (Quality of Services) methods to assess the quality of bandwidth management of internet network services at Shanti Bhuana Institute. The findings of this study can be used to make physical recommendations for the internet network of the Shanti Bhuana Institute. Based on measurements and tests carried out on the internet network at the Shanti Bhuana Institute, a throughput value of 6721 kb/s was obtained. This figure is part of the very good category index. Meanwhile, the amount of packet loss is very low (0.0001%), so it is classified as very good, the delay obtained is 50.338539 ms which is included in the very good category, while the jitter value is 52.97569 ms which is included in the good category.